2021
DOI: 10.1016/j.jamda.2021.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Coronavirus Disease 2019 Vaccination Condition of Employment in a Community Nursing Home

Abstract: The rate of COVID-19 vaccination uptake by U.S nursing home staff remains low despite the increased risks of viral transmission and related morbidity and mortality in this setting. This study describes vaccine uptake activities including a COVID-19 Vaccination Condition of Employment (COE) policy in one community nursing home. This case study summarizes the timeline of vaccination uptake activities, staff vaccination rates over time, and stakeholder perspectives around the implementation of a COVID-19 Vaccine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…The majority of participants (79% in surveys) discussed visiting restrictions as a key stressor, and only 21% highlighted alternative visiting modalities as a helpful strategy. Instead of focusing on communication workarounds, maximizing opportunities to visit in-person with the help of consistently enforced vaccination 42 and testing may be more helpful to family caregivers. 32 , 34 As LTC facilities navigate emerging COVID-19 outbreaks, prioritizing in-person visits will be crucial for maintaining residents' well-being.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of participants (79% in surveys) discussed visiting restrictions as a key stressor, and only 21% highlighted alternative visiting modalities as a helpful strategy. Instead of focusing on communication workarounds, maximizing opportunities to visit in-person with the help of consistently enforced vaccination 42 and testing may be more helpful to family caregivers. 32 , 34 As LTC facilities navigate emerging COVID-19 outbreaks, prioritizing in-person visits will be crucial for maintaining residents' well-being.…”
Section: Discussionmentioning
confidence: 99%
“…An equally high proportion of respondents agreed that COVID-19 vaccination should be required for visiting nursing homes and working in healthcare settings to reduce the risk to vulnerable people. In the US, a case study demonstrated that a COVID-19 vaccination condition of employment should be implemented with caution, as it required efforts and involvement from staff at all levels of the workplace, adequate time for developing and disseminating information, transparent communication and sufficient funding [33]. Compared to a previous survey reporting that 73% agreed that the Government should require a COVID-19 vaccine for work, travel and study in 2020, our survey showed a lower level of support for possible Government mandates (54% strongly or somewhat agreed).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that implementation of vaccine mandates could promote resignations among some workers. Recent case study evidence, however, suggests that the adverse impact of vaccine mandates for retention may be minimal in the context of strong support and communication on the part of nursing home leadership (Ritter et al, 2021).…”
Section: Economic Effects and Older Adultsmentioning
confidence: 99%